A bridge too far: yoga, spirituality, and contested space in the Pacific Northwest. Issue 4 (20th October 2019) - Bramadat, Paul
ABSTRACT: In 2015 a plan to celebrate the inaugural International Day of Yoga in Vancouver generated a powerful backlash. What might have been for some a public expression of their interest in a trendy wellness activity, and for others a meaningful demonstration of an important spiritual practice, was cancelled just a week after it was announced. How did this single postural yoga class so quickly and definitively galvanise public opinion, and what can this teach us about the machinations of public discourse? In this brief but revealing controversy, most interlocutors focused on local political considerations, paying somewhat less attention to the now common critique that postural yoga is elitist and vapid, and virtually none to claims and metaphors related to spirituality that circulated widely among practitioners and promoters. This incident may remind us that religious and spiritual claims are not sui generis but always part of larger social discourses that reveal a great deal about quite this-worldly concerns, interests, and values.